Changes in natriuretic peptides after acute hospital presentation for heart failure with preserved ejection fraction: A feasible surrogate trial endpoint? A report from the prospective Karen study. (1st January 2017) - Savarese, Gianluigi; Donal, Erwan; Hage, Camilla; Oger, Emmanuel; Persson, Hans; Daubert, Jean-Claude; Linde, Cecilia; Lund, Lars H.; ,
Abstract: Background: In acute decompensated heart failure (ADHF) with preserved ejection fraction (HFpEF) there are no surrogate endpoints for early phase trials. The aim of the current study was to evaluate whether a reduction in natriuretic peptides (NP) between acute hospital presentation to stable follow-up is associated with improved mortality and morbidity. Methods: Patients presenting acutely to the hospital for ADHF with HFpEF enrolled in the Karolinska Rennes (KaRen) study and reporting N-terminal pro-B-type NP or B-type NP assessment at baseline hospital presentation and at 4–8 weeks follow-up were prospectively studied. Logistic regression analyses were performed to detect the predictors of baseline and changes in NPs. Cox regression models were performed to assess the impact of NP reductions on mortality and the composite of mortality and HF hospitalization. Results: Of 361 patients (median follow-up 585 days), 267 (74%) reported an improvement in NPs, while 94 (26%) reported worsening. At baseline, the independent predictors of lower NPs were higher glomerular filtration rate (Odds Ratio [OR] per unit: 1.013; 95% Confidence Interval [CI]: 1.005–1.021) and younger age (OR per year: 0.972; CI: 0.947–0.998). Improvement in NPs at follow-up was predicted by higher heart rate at baseline (OR per bpm: 1.014; CI: 1.003–1.025). After adjustments, the hazard ratio for all-cause death was 0.730 (CI: 0.456–1.169) and for the composite outcome 0.814 (CI: 0.582–1.139) for patients who improved vs. worsened in NP levels. Conclusions: In patients presenting acutely to the hospital with HFPEF, an improvement in NP levels did not independently and significantly predict improved mortality and/or morbidity. NPs as surrogate endpoints in acute HFpEF require further study.